2019
DOI: 10.1242/dmm.039669
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate alters the vaginal microbiota and microenvironment in women and increases susceptibility to HIV-1 in humanized mice

Abstract: The hormonal contraceptive medroxyprogesterone acetate (MPA) is associated with increased risk of human immunodeficiency virus (HIV), via incompletely understood mechanisms. Increased diversity in the vaginal microbiota modulates genital inflammation and is associated with increased HIV-1 acquisition. However, the effect of MPA on diversity of the vaginal microbiota is relatively unknown. In a cohort of female Kenyan sex workers, negative for sexually transmitted infections (STIs), with Nugent scores <7 (N=58 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 61 publications
(132 reference statements)
4
42
0
1
Order By: Relevance
“…The NRF-2 is a pathway of defense against oxidative stress; downstream effects lead to increased glucose metabolism [ 49 ], and this pathway can be influenced by progestins [ 50 ]. Indeed, DMPA has been associated with altered glucose metabolism [ 51 ] and type-2 diabetes [ 52 ]. Glucose metabolism has previously been shown to be important for the recruitment and activation of CD4 + T cells [ 53 ], and studies have suggested that glycolysis is an important pathway in the CD4+ T cell immune response [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRF-2 is a pathway of defense against oxidative stress; downstream effects lead to increased glucose metabolism [ 49 ], and this pathway can be influenced by progestins [ 50 ]. Indeed, DMPA has been associated with altered glucose metabolism [ 51 ] and type-2 diabetes [ 52 ]. Glucose metabolism has previously been shown to be important for the recruitment and activation of CD4 + T cells [ 53 ], and studies have suggested that glycolysis is an important pathway in the CD4+ T cell immune response [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, use of progestin-based hormonal contraception has been associated with a reduction in incidence of BV [ 32 , 58 , 59 ], and higher levels of vaginal Lactobacillus spp. [ 29 ]; however, others have reported a decrease the levels of vaginal H 2 O 2 -producing lactobacilli [ 43 , 60 , 61 ], increases in microbial diversity [ 51 ], or no effect on microbiome composition [ 62 ]. We observed only minor differences in microbiome composition and no changes to microbiome-derived functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis of observational data for DMPA-IM relative to no contraception or mainly condom use are currently the best estimate of the HIV risks associated with DMPA-IM and are mostly consistent with a large body of other clinical, animal, and laboratory studies indicating several plausible biological mechanisms whereby DMPA-IM may increase HIV acquisition relative to no contraception. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]72 The ECHO trial results on relative HIV risks between the three methods are subject to several limitations and uncertainties. They provide evidence that the LNG implant may be associated with lower HIV risk than DMPA-IM and the copper-IUD.…”
Section: What Do the Echo Results Tell Us About The Risks Of Hiv Acqumentioning
confidence: 99%
“…Briefly, these mechanisms include modification of the protective epithelial barrier lining the female genital tract, altered genital immunity and defense (cytokines, chemokines, defensins, antibodies, etc. ), a change in HIV-1 target cell activation or frequency (T cells, dendritic cells (DCs), and macrophages), and most recently modification of the vaginal microbiota 13 , 14 . We recently characterized and described an intravaginal infection model of HIV-1 in humanized mice 15 (Hu-mice) where we demonstrated that frequency of human CD45+ target cells was the primary determinant of HIV-1 infection following intravaginal inoculation, and that viral dose was a determinant of viral dissemination and plasma titres during early infection 15 .…”
Section: Introductionmentioning
confidence: 99%